2017
DOI: 10.1177/0013124517713250
|View full text |Cite
|
Sign up to set email alerts
|

STEM Teaching and Learning Strategies of High School Parents With Homeschool Students

Abstract: The purpose of this research study was to investigate the teaching and learning strategies used by homeschool parents with high school students. A qualitative case study was used which began with the administration of an open-ended questionnaire to a homeschool community in the southern United States. Twenty-nine parents completed the questionnaire, and 10 of those volunteered to participate in the follow-up procedures, which included interviews, observations, and document collection. Results indicate that par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…One of the values of the homeschooling approach is the ability to tailor curricula to a student's particular needs and learning style. Research has found that homeschooling parents "use a variety of teaching and learning strategies including individualized instruction, mastery learning, self-directed study, collaboration with peers and adults, and application and connection of information" (Gann & Carpenter, 2018). Cardinale (2015) found similar attributes, including, "strong nuclear families, direct teaching, self-study or self-directed education, mastery learning, purposive conversations, and challenging curriculum" helped homeschooled children succeed (p. 3).…”
Section: Values Of Homeschoolingmentioning
confidence: 99%
“…One of the values of the homeschooling approach is the ability to tailor curricula to a student's particular needs and learning style. Research has found that homeschooling parents "use a variety of teaching and learning strategies including individualized instruction, mastery learning, self-directed study, collaboration with peers and adults, and application and connection of information" (Gann & Carpenter, 2018). Cardinale (2015) found similar attributes, including, "strong nuclear families, direct teaching, self-study or self-directed education, mastery learning, purposive conversations, and challenging curriculum" helped homeschooled children succeed (p. 3).…”
Section: Values Of Homeschoolingmentioning
confidence: 99%
“…Furthermore, he revealed that in compiling the methods and design of learning process, the parents should consider the characteristics of their child. The research conducted by Gann & Carpenter (2017) also assumed that the parents use a variety of teaching learning strategies including individual instruction, defense understanding, self-study, collaboration among their peers and adults as well as the application and connection of information as one method of arranging learning at home. Tuzun, Soylu, Karakus, Inal, & Kizilkaya (2009) in their research found that the application of computer games toward the students' geography in learning at elementary school significantly increased especially the students' learning motivation through games as a learning method.…”
Section: Collecting Available Resourcesmentioning
confidence: 99%
“…Ideologues instead have a desire to teach conservative religious values (Van Galen, 1988). More recent studies report a wide array of motivations to educate at home (Gann & Carpenter, 2017;Hanna, 2012;Harding, 2011). Some suggest ubiquitous access to educational materials made possible by the Internet (Bullock, 2011;McAvoy, 2015;New South Wales Parliament, 2014) help account for the recent growth in home-education; growth witnessed in Australia (Chapman, 2017) and elsewhere (Issimdar, 2018;Neuman & Guterman, 2013).…”
Section: Introductionmentioning
confidence: 99%